Numerical Prediction of Extreme Precipitation over a Truly Complex Terrain of Nepal Himalaya - Maharjan, Sangeeta; Regmi, Ram R (Journal of Institute of Science and Technology, 2015)
The predictability of extreme precipitation over truly complex terrain of Nepal Himalaya using Weather Research and Forecasting (WRF) Modeling System has been examined with the case study of record high precipitation (357 mm in 24-hours) over the Pokhara area on the day of 18 August 2001 initialized with NCEP Reanalysis Global Data sets of 1° x 1° resolution without appreciating observation data assimilation. The model resolved the essential features of the precipitation pattern over the area although the model underestimated the reported amount of precipitation as much as 87 mm. The difference may be attributed to the highly localized intense precipitation due to local effects. Significant improvement in the accuracy of prediction can be expected with detail regional meteorological data assimilation. Journal of Institute of Science and Technology, 2015, 20(1): 15-19